Web-based software application design for solar PV system sizing - Lambe Mutalub Adesina; Olalekan Ogunbiyi; Mustapha Mubarak (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The solar photovoltaic (PV) energy source systems generally rely on the availability of sunlight, its duration, and the capacity of storage devices if it is not a grid-tie system. The components of the PV sources come in different sizes and capacities, depending on the various applications and available products in the market. Therefore, sizing of PV components becomes important to the functionality and reliability of solar PV sources. This work is aimed at the development of a web-based software application designed for sizing the capacity of solar PV source components that meet required energy demand. A description of photovoltaic system components, available types, and sizing techniques are discussed. Parameter evaluation algorithms with flowcharts were developed for PV components. Consequently, web-based software was developed and simulated for a different case study. The results described the estimated load, average daily load, ratings of PV system components such as inverter, battery, solar panel, and charge controller. The cost estimates of each component, the total estimated cost of the project, and the specification of components’ purchasing store are similarly presented. Thus, the developed application can be applied to size different ranges of microgrid systems meant for several applications.